Clinical Effect of Hufu Copper Scraping on Shoulder-Hand Syndrome after Stroke - Lianyi He; Xinyu Chen; Yuejuan Zhang (Emergency Medicine International)
Objective. To explore the clinical effect of Hufu copper scraping on shoulder-hand syndrome after stroke. Methods. A total of 60 patients with shoulder-hand syndrome after stroke admitted to the First Affiliated Hospital of Hunan University of Traditional Chinese Medicine were enrolled between January 2020 and June 2021. According to the random number table method, they were divided into the control group (n = 30) and the intervention group (n = 30). The control group was given routine rehabilitation intervention, while the intervention group was additionally given Hufu copper scraping. The intervention effect, occurrence of adverse reactions during the intervention, pain, swelling degree of affected hands, serum calcitonin gene-related peptide (CGRP), substance P (SP), and Barthel index before and after 2 months of intervention were compared between the two groups. Results. After intervention, the total response rate of the intervention group was significantly higher than that of the control group (96.67% vs 80.00%) (P<0.05). After intervention, the score of the visual analogue scale (VAS) and water displacement in the intervention group were lower than those in the control group (P<0.05). After intervention, levels of CGRP and SP in the intervention group were lower than those in the control group, while the Barthel index was higher compared to the control group (P<0.05). Conclusion. The intervention effect of Hufu copper scraping is good, which can promote the recovery of related symptoms, relieve pain and swelling of affected hands, downregulate levels of disease-promoting markers, and accelerate recovery of related function in patients with shoulder-hand syndrome after stroke.